Physiological Functions of the β-Site Amyloid Precursor Protein Cleaving Enzyme 1 and 2 - Yan, Riqiang (Frontiers in Molecular Neuroscience, 2017)
BACE1 was discovered as the β-secretase for initiating the cleavage of amyloid precursor protein (APP) at the β-secretase site, while its close homology BACE2 cleaves APP with the Aβ domain region and shows distinct cleavage preferences in vivo. Inhibition of BACE1 proteolytic activity has been confirmed to decrease Aβ generation and amyloid deposition, and thus specific inhibition of BACE1 by small molecules is a current focus for Alzheimer’s disease therapy. While BACE1 inhibitors are being tested in advanced clinical trials, knowledge regarding the properties and physiological functions of BACE is highly important and this review summarizes advancements in BACE1 research over the past several years. We and others have shown that BACE1 is not only a critical enzyme for testing the “Amyloid Hypothesis” associated with Alzheimer’s pathogenesis, but it also important for various functions such as axon growth and pathfinding, astrogenesis, neurogenesis, hyperexcitation, and synaptic plasticity. BACE2 appears to play different roles such as glucose homeostasis and pigmentation. This knowledge regarding BACE1 functions is critical for monitoring the safe use of BACE1 inhibitors in humans.